(-3)-2.2-9-(-12)=

Simple and best practice solution for (-3)-2.2-9-(-12)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3)-2.2-9-(-12)= equation:


(-3)-2.2-9-(-12)=0

We simplify the equation to the form, which is simple to understand
(-3)-2.2-9-(-12)=0

Remove unnecessary parentheses
-3-2.2-9-(-12)=0

Remove unnecessary parentheses
-3-2.2-9+12=0

We move all terms containing to the left and all other terms to the right.
0=0+3+2.2+9-12

We simplify left and right side of the equation.
0=+2.2

0=2.2

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 8x-5=2(4x-3) | | 2.2x=-22 | | 3x+12=-3x+20 | | 2(3x+1)+4=2-x | | 18x+2(x+7)=-6 | | 37+12+=85 | | 7x+9=4x+3 | | 0.3x+1.1=3.5 | | 2*(3-x)+7=4x-5*(2+x) | | 0.3+1.1=3.5 | | 2(3-x)+7=4x-5(2+x) | | 5x=3x+20 | | 32-3x=2x-28 | | (22b-9)-7(3b+4)=-4 | | 3x-4(x-2)(X^2+6x^2-1)-7= | | 4x+2-3x=18 | | 5a(a+3)=2a(2a-5) | | 2(3+2w)+1=-5 | | x(x-4)+56=x*x | | 8x+2=3x-2 | | -9x+11=2x+11 | | 7e+10=4e+28 | | 6x^3-6x+1=0 | | -7x+1=-13 | | Y=3.5 | | 8h+9=3h+54 | | 0.125f=0.1875 | | 3x+1.2=3.9 | | (-2)-(-6)-4= | | 4v+7=2v+15 | | 5x+5=(x-1) | | 2+2=7-3 |

Equations solver categories